1985
DOI: 10.1111/j.1471-0528.1985.tb01113.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced in‐vitro fertilization of human oocytes from patients with raised basal luteinizing hormone levels during the follicular phase

Abstract: Reduced in-vitro fertilization of human oocytes from patients with raised basal luteinizing hormone levels during the follicular phase 58, 203-212. Vandenberg, J . L. & Y e n , S. S. (1973) Effect of antioestrogenic action of clomiphene during the menstrual cycle: evidence for a change in the feedback sensitivity. J Clipl Endocrind Mercrh 37, 356-365. Whittingham, D . (1971) Culture of mouse ova. J Reprod Fertil 14, [Suppl.] 7-21,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
1
4

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 364 publications
(92 citation statements)
references
References 23 publications
(3 reference statements)
3
84
1
4
Order By: Relevance
“…Kolbianakis et al have suggested that high concentrations of LH or exposure to high levels of LH and E2 in the early follicular phase may exert detrimental effects on the success of ovulation induction and conception, thus functioning as a causal factor in early pregnancy loss (21)(22)(23)(24). This is feasible either by introducing antagonist administration earlier in the cycle or pretreating patients with the oral contraceptive pill, thus suppressing gonadotropins at the start of stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Kolbianakis et al have suggested that high concentrations of LH or exposure to high levels of LH and E2 in the early follicular phase may exert detrimental effects on the success of ovulation induction and conception, thus functioning as a causal factor in early pregnancy loss (21)(22)(23)(24). This is feasible either by introducing antagonist administration earlier in the cycle or pretreating patients with the oral contraceptive pill, thus suppressing gonadotropins at the start of stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest that high concentrations of LH during the follicular phase of stimulation can have a negative impact on oocyte quality, pregnancy rate and incidence of miscarriage (Stanger and Yovich, 1985; Howies © European Society for Human Reproduction and Embryology et al, 1986;Homburg et al, 1988;Regan et al, 1990;Shoham et al, 1990). Several centres therefore substituted HMG partially or completely by pure FSH (Venturoli et al, 1986;Diedrich et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…A significant reduction in the rate of fertilization was observed in women with raised basal LH levels (greater than one standard deviation from the mean) undergoing treatment with IVF with ovarian stimulation using clomiphene citrate (CC), hMG or a combination of the two 13 . In another study, in women undergoing IVF treatment with a combination of CC and hMG, there were no pregnancies recorded if the urinary output of LH was elevated when measured two days prior to the day of hCG administration 14 .…”
Section: Discussionmentioning
confidence: 99%